REPRESENTASI BUDAYA LOKAL DALAM KEGIATAN DENPASAR FESTIVAL DI KOTA DENPASAR - Eka Juliawati, Ni Putu (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies), 2012)
This paper discusses the representation of local culture inDenpasar Festival. Denpasar Festival is Denpasar’s Governmentannual agenda which aimed at reviving the local culture ofDenpasar which more and more faded because it underminedby globalization. The increasing arrival of tourists and migrantshave been destabilizing the existence of Denpasar local culture.Denpasar Festival was serving traditional cuisine, dance andperforming arts and traditional textiles. Based on this background, the problem of this study is what were the implications of the representation of local culture in Denpasar Festival?This study was a qualitative interpretative research. Thedata were collected through field observations, interviews andliterature study. The theories used were the representation theory and theory of deconstruction. As a result of this study, it was found that Denpasar Festival has implications for the social, cultural and economic fields.